Comprehensive review of breast cancer risk factors, diagnosis, screening, and treatment methods - Hoque, Nurjamal; Choudhury, Ananta; Baishya, Dhiraj; Deka, Himangshu (Creative Pharma Assent, 2024)
Background: Breast cancer is one of the leading causes of cancer-related deaths among women, accounting for 11.7% of all cancer cases and approximately 685,000 deaths worldwide in 2020. Its multifactorial etiology includes genetic, hormonal, and lifestyle-related risk factors with significant implications for diagnosis and treatment. Understanding these factors and the latest advancements in screening and therapeutic approaches is essential for improving patient outcomes. Methodology: This review synthesizes findings from peer-reviewed articles, clinical trials, and meta-analyses. The focus is on identifying key risk factors for breast cancer, evaluating the effectiveness of current diagnostic methods, and examining the latest treatment strategies, including personalized medicine. Data were collected from PubMed, Scopus, and Google Scholar databases. Results and Discussion: The review highlights major risk factors, including BRCA1/BRCA2 mutations, which contribute to a 45-65% lifetime risk, as well as hormonal influences and lifestyle factors like obesity and alcohol consumption. Targeted therapies, such as HER2 inhibitors (e.g., trastuzumab) and hormone therapies (e.g., tamoxifen), have significantly improved survival rates. Emerging treatments like immunotherapy and PARP inhibitors are also promising for aggressive and metastatic cases. Conclusion: Breast cancer continues to pose a significant health challenge, but advancements in risk assessment, early detection, and personalized treatment offer hope for better outcomes. Continued research and refining diagnostic and therapeutic approaches are essential for reducing breast cancer mortality and enhancing patient quality of life.